2016
DOI: 10.2147/ott.s106508
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase M2 overexpression and poor prognosis in solid tumors of digestive system: evidence from 16 cohort studies

Abstract: PurposeThe expression of pyruvate kinase M2 (PKM2) has been linked to tumor formation and invasion. Specifically, the relationship between high PKM2 expression and prognosis has been evaluated in solid tumors of digestive system. However, the prognostic value of PKM2 remains controversial.MethodsA literature search of PubMed, Embase, and Cochrane databases was conducted until October 2015. The end point focused on overall survival (OS). The pooled hazard ratio (HR) or odds ratio and the 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…The synthesized data suggested that decreased level of serum apoA1 was significantly correlated with some phenotypes of tumor progression, such as larger tumor size, poor histological grade, and advanced clinical stage. All these aggressive tumor behaviors have been documented to be independent factors related to tumor progression and compromise survival outcome [49, 50]. Herein, apoA1 played an important role in the inhibition of tumor progression through different pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized data suggested that decreased level of serum apoA1 was significantly correlated with some phenotypes of tumor progression, such as larger tumor size, poor histological grade, and advanced clinical stage. All these aggressive tumor behaviors have been documented to be independent factors related to tumor progression and compromise survival outcome [49, 50]. Herein, apoA1 played an important role in the inhibition of tumor progression through different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The result was considered statistically significant if the 95% CI did not overlap 1. Heterogeneity was qualitatively examined through the chi-squared Q test and quantitatively estimated using the I 2 metric ( I 2 < 25%, no heterogeneity; I 2 = 25% – 50%, moderate heterogeneity; I 2 > 50%, extreme heterogeneity) [24]. When significant heterogeneity was observed ( P < 0.05 or I 2 > 50%), a random-effects model was used to calculate the pooled HR estimation.…”
Section: Methodsmentioning
confidence: 99%
“…PKL and PKR are mainly expressed in liver cells and erythrocytes, respectively, whereas PKM1 is constitutively expressed in normal cells. The over-expression of PKM2 was frequently observed in malignances and predicts worse prognosis[31,32]. A recent study demonstrated that the expression of PKM2 is up-regulated in HCC and is a predictor of survival and recurrence[33].…”
Section: Reprogramming Of Glucose Metabolism-related Enzymes and Tranmentioning
confidence: 99%
“…Additionally, PKM2 has been reported to function as a protein kinase to regulate gene transcription in nuclei (Jiang et al, 2014;Yang et al, 2012) and reprogram oxidative phosphorylation to aerobic glycolysis to promote tumor cell proliferation and migration in mitochondria . Overexpression of PKM2 has been universally found in human cancers and associated with poor clinical outcomes (Li et al, 2014a;Lim et al, 2012;Wu et al, 2016). Furthermore, PKM2 has been found in the extracellular fluid of patients with gastrointestinal cancer, pancreatic ductal adenocarcinoma, lung cancer, ovarian cancer, and renal cell carcinoma (Amin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%